Protein Engineering - Kaumaya, Pravin (IntechOpen, 2012)
A broad range of topics are covered by providing a solid foundation in protein engineering and supplies readers with knowledge essential to the design and production of proteins. This volume presents in-depth discussions of various methods for protein engineering featuring contributions from leading experts from different counties. A broad series of articles covering significant aspects of methods and applications in the design of novel proteins with different functions are presented. These include the use of non-natural amino acids, bioinformatics, molecular evolution, protein folding and structure-functional insight to develop useful proteins with enhanced properties.